El control de inventarios y su incidencia en la rentabilidad del comercial avícola rincón de España, cantón Quinindé, período 2018. - Cintia Johana, Benítez López (2021)
ABSTRACT This research work is based on the evaluation of inventory control and its impact on the profitability of the poultry commercial "Rincón de España" of the Quinindé canton, period 2018, in order to evaluate inventory control and identify the products that generate greater profitability and avoid differences in the reports presented, which influence decision-making. The research was developed, starting with the problem statement to establish the objectives and reasons why the commercial must be studied. In the theoretical framework, state of the art and the commercial's generalities are detailed for the identification of the study variables. The inductive method was applied to detect existing problems from the observation of particular facts. It is a documentary and field research that allows obtaining information from external documents and its documents. It was non-experimental research because there was no manipulation of the variable under study. The approach is qualitative because it was possible to obtain specific information through the application of the survey. The research level was descriptive since it allowed us to observe the situations and events in 2018. As a result, obtained in this investigation, it is detected that a good administration in the control of inventories will allow controlling the movements of the same and reflect in the Financial Statements real information of the commercial. Keywords: Inventories, Inventory Control, Accounting, Financial Statements Reviewed by: Mgs. Lorena Solís ENGLISH PROFESSOR C.C. 0603356783